Plectranthias raki (Teleostei, Serranidae), a new species of perchlet from mesophotic coral ecosystems of the Maldives - Bart Shepherd; Hudson T. Pinheiro; Ahmed Najeeb; Claudia R. Rocha; Luiz A. Rocha (ZooKeys)
Herein, we describe a new species of Plectranthias perchlet found at depths of 100–125 meters in mesophotic coral ecosystems of the Maldives in the Indian Ocean. Plectranthias raki sp. nov. is unique in both morphology and coloration. The following combination of characters distinguishes it from all known congeners: dorsal fin X, 15; anal-fin rays III, 7; pectoral-fin rays 13 | 13 (13 | 12), all unbranched; principal caudal-fin rays 9 + 8; lateral line complete with 30–32 tubed scales; gill rakers 5 + 12; circumpeduncular scales 11–12; and absence of antrorse or retrorse spines on ventral margin of preopercle. Coloration in life consists of a white to light pink body with two indistinct rows of irregularly shaped red-orange to yellow-orange patches along the dorsal two-thirds of the body, a golden-yellow opercle and maxilla, an indistinct yellow stripe on the dorsal fin, two yellow spots near the base of the anal fin, and two irregularly shaped yellow-orange spots located on either side of centermost caudal-fin rays. With this publication, the genus Plectranthias now comprises 67 valid species. This discovery adds to a strong body of research highlighting the novel biodiversity of mesophotic ecosystems, especially in locations like the Indian Ocean, where few prior ichthyological surveys have been conducted.